Technological maturity and future perspectives for green diesel production in Brazil - Lucas Sudré dos Santos; Henrique Gasparetto; Nina Paula Gonçalves Salau (Cleaner Chemical Engineering)
During technological and social development, non-renewable sources were used to generate energy in various forms. The overexploitation of fossil fuel sources has raised significant concerns about environmental impacts. Given the need to transition to developing a more sustainable energy matrix, biofuels play an essential role as the transport sector contributes to a large percentage of gas emissions into the atmosphere. Among them, green diesel is an advanced biofuel obtained on an industrial scale, mainly by the catalytic hydrotreating of vegetable oils. In terms of technology and properties, green diesel stands out as a drop-in biofuel, which lacks blending restrictions with conventional diesel due to its chemical similarity. This biofuel also contains fewer impurities and has better combustion performance and an efficient production process. The leading green diesel manufacturing technologies are the main topic of this technological prospection review. Their particularities regarding industrial maturity are discussed, and challenges, opportunities, and drawbacks are considered and discussed for the Brazilian scenario. This analysis shows that although existing technologies have higher technological maturity, Brazil would have a special tendency toward catalytic hydrotreating for producing renewable diesel.